Economic Development of Bangladesh: The Role of IBBL - Rahman, Shafiqur; McDonald, Nicholas (IIUC Studies, 2015)
This paper presents the role of Islami Bank Bangladesh Limited (IBBL) to the recent economic development in Bangladesh. The study analyses published texts, articles, websites and annual report of this bank through a content analysis. Key findings of this study manifest the contribution of this bank in different areas of economic development in Bangladesh like generating employment, earning foreign remittance, strengthening rural economy, promoting ecology and green banking, boosting industrialization, developing the SMEs, assisting in foreign trade (import-export), developing the housing sector etc. This study also identifies IBBLs significant contribution to the national exchequer. This paper contributes to the field of economic development of Bangladesh and the role of IBBL behind it and fills the gap of literature in this specific area. IIUC Studies Vol.9 December 2012: 323-334